Quantitative analysis of expression level of estrogen and progesterone receptors and VEGF genes in human endometrial stromal cells after treatment with nicotine. (12th October 2016) - Totonchi, Hamidreza; Miladpour, Behnoosh; Mostafavi-Pour, Zohreh; Khademi, Fatemeh; Kasraeian, Maryam; Zal, Fatemeh
Abstract: Cigarette smoke is a complex mixture of toxic chemicals, including nicotine, carbon monoxide, and several recognized carcinogens and mutagens. Nicotine has a direct disturbing influence on steroid hormones (estrogen and progesterone), which are essential components of the female reproductive system, but the effect of nicotine on the hormone receptors is not yet clear. The aim of this study was to elucidate the effect of nicotine on the expression of estrogen receptor (ER), progesterone receptor (PR), and vascular endothelial growth factor (VEGF) in endometrial stromal cells. Expression levels of PR, ER, and VEGF in human endometrial stromal primary cells treated with nicotine (0, 10 −11, 10 −8, and 10 −6  μM) for 24 h were measured by quantitative real-time PCR. MTT assay demonstrated that nicotine decreased cell viability in a dose-dependent manner. Real-time PCR data showed that despite decrease in ER expression in the nicotine-treated groups compared with the control, nicotine exerted an increased inhibitory effect on PR expression compared to that on ER expression. VEGF mRNA expression in nicotine-treated endometrial stromal cells was increased. The results from this study provide novel evidence for inhibitory effects of nicotine on steroid hormones receptor expression in human primary endometrial cells. Also, our data suggest that nicotine might have angiogenesis effects on these cells.